Intra-Operative Activation of Coagulation - A Stimulus to Thrombosis Mediated by Vasopressin? - Grant, P J; Tate, G M; Davies, J A; Williams, N S; Prentice, C R M (Thrombosis and Haemostasis, 1986)
Vasopressin infusions in normal volunteers that produce concentrations in plasma comparable to those seen during stress, cause an increase in plasma factor VIII and shortening of the euglobulin clot lysis time (ECLT). We have investigated the relationship between endogenous vasopressin (aVP) release and haemostatic function in 7 patients undergoing major abdominal surgery. Blood samples were taken at nine intervals during the operative procedure. Plasma aVP levels peaked at median values of 51 pg/ml during bowel manipulation and remained elevated on the first post-operative day. Following, and in close temporal relationship with the rise in aVP there were increases in factor VIII coagulant activity, the ristocetin co-factor, von Willebrand antigen, plasminogen activator activity (106/ECLT2) and fibrinopeptide A concentrations with shortening of the activated partial thromboplastin time. The relationship was similar to that seen following infusion of a VP in human volunteers. The results are consistent with the hypothesis that aVP is an important mediator of changes in haemostatic function which accompany stress and might contribute to the thrombotic risk associated with surgical operations.
Keywords: Abdominal surgery; Vasopressin; Factor VIII; Fibrinolysis; Fibrinopeptide A